Heterogeneity in Price Elasticity of Medicine Demand in China: Moderate Effect From Economic Incentive and Quality Difference - Mingyue Zhao; Mingyue Zhao; Peng Nie; Jing Wu (Frontiers Media S.A., 2021)
Objectives: Previous studies have shown a wide range of drug price elasticity, but the price response to demand among various therapeutic drug categories and drug types (generic/originator) is still unexplored in China. This study estimates the price elasticity of medicine demand with regard to quality differences, unfair competition, and a regulated market.Methods: Product-level data on anti-tumor, cardiovascular disease (CVD), and antimicrobial drugs were collected from the Tianjin Urban Employees' Basic Medical Insurance database (2008-2010). The moderating effects of quality, profit incentive, and illegal rebates are considered in a dynamic panel model.Findings: Our results suggest that the price elasticity of drug demand varies across drug categories, with least elasticity for anti-tumor drugs and most elasticity for CVD drugs (−0.192 for anti-tumor drugs vs. −0.695 for antimicrobials vs. −1.100 for CVD drugs, p < 0.01). Moreover, the absolute value of price elasticity of generic drugs is higher than that of originator drugs in anti-tumor and CVD therapeutic classes (interact: 0.716 for anti-tumor; -0.630 for CVD, p < 0.001). We believe that quality difference plays a dominant role in the interaction between quality and illegal rebates for these two kinds of generic drugs. In the antimicrobial sub-group, the absolute value of price elasticity of generic medicine is lower than that of originator drugs. We believe that, owing to the high level of unfair competition among enterprises, the role of illegal kickbacks is dominant, which reduces the price elasticity of demand for generic antimicrobial drugs.Conclusion: Our study provides an overview of the result of interaction between quality and illegal rebates in different medicine markets in China and shows that disease type is a primary factor that impacts price elasticity.